2023
DOI: 10.3389/fnins.2023.1103437
|View full text |Cite
|
Sign up to set email alerts
|

Engineering circuits of human iPSC-derived neurons and rat primary glia

Abstract: Novel in vitro platforms based on human neurons are needed to improve early drug testing and address the stalling drug discovery in neurological disorders. Topologically controlled circuits of human induced pluripotent stem cell (iPSC)-derived neurons have the potential to become such a testing system. In this work, we build in vitro co-cultured circuits of human iPSC-derived neurons and rat primary glial cells using microfabricated polydimethylsiloxane (PDMS) structures on microelectrode arrays (MEAs). Our PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…We observed that neurons avoided regions patterned with PMOXA and preferentially grew on locations with PLL. While this patterning approach on MEAs is less effective than the use of microstructures, 23,24,43,44 our results serve as a proof-of-concept that surface patterns on MEAs can be induced in situ to introduce neural guidance at unprecedented spatial resolutions in vitro . Microstructures excel in the guidance of neurons due to their three-dimensional physical confinement of neurons.…”
Section: Discussionmentioning
confidence: 80%
“…We observed that neurons avoided regions patterned with PMOXA and preferentially grew on locations with PLL. While this patterning approach on MEAs is less effective than the use of microstructures, 23,24,43,44 our results serve as a proof-of-concept that surface patterns on MEAs can be induced in situ to introduce neural guidance at unprecedented spatial resolutions in vitro . Microstructures excel in the guidance of neurons due to their three-dimensional physical confinement of neurons.…”
Section: Discussionmentioning
confidence: 80%